Breast cancer during pregnancy - Acharya, Sandhya C.; Shah, Aarati (Grande Medical Journal, 2019)
Breast cancer during pregnancy is rare accounting for 1 in around 3000 pregnant women as per the American cancer society. According to hospital-based cancer registry of Nepal, breast cancer accounts for 9.2% of total cancer cases and pregnancy associated breast cancer accounts for 0.15% of the total breast cancer. Though rare, breast cancer is the most common type of cancer found during pregnancy and that too in advanced stage because of the hormonal interplay during pregnancy. Here we present a case of breast cancer during pregnancy which was treated successfully with chemotherapy, surgery, radiation therapy and is on hormonal treatment. Patient is on regular follow up for the last six years without evidence of recurrence of the disease, and the baby has achieved normal developmental milestones though exposed to chemotherapy in utero.